2017
DOI: 10.1016/j.placenta.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of the chromosome 21 MicroRNA cluster (miR-99a, miR-125b and let-7c) in chorioamniotic membranes

Abstract: Trisomy 21 (T21) is the most common chromosome abnormality in humans and is associated with a spectrum of phenotypes, including cognitive impairment, congenital heart defects and immune system defects. In addition, T21 is also associated with abnormalities of fetal membranes including chorioamniotic separation, delayed fusion of the chorioamniotic membranes, defects in syncytiotrophoblast formation, as well as amniocyte senescence. There is evidence indicating miRNAs encoded by sequences on chromosome 21 (Chr-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…Our data above showed that young iEVs but not aging iEVs decreased splenic Th17 cells likely through M2 macrophage polarization and consequent increase in the IL1 antagonist IL1rn ( Figure 3 ). Notably, IL1rn is a putative target of miR-125b [ 32 ]. To determine effects of miR-125b inhibition in aging iEVs on splenic Th17 cells, we examined IL17 + Th cells from NOD.B10.H2 b mice at 2 weeks after IV infusion of Ctrl or 125KD aging iEVs.…”
Section: Resultsmentioning
confidence: 99%
“…Our data above showed that young iEVs but not aging iEVs decreased splenic Th17 cells likely through M2 macrophage polarization and consequent increase in the IL1 antagonist IL1rn ( Figure 3 ). Notably, IL1rn is a putative target of miR-125b [ 32 ]. To determine effects of miR-125b inhibition in aging iEVs on splenic Th17 cells, we examined IL17 + Th cells from NOD.B10.H2 b mice at 2 weeks after IV infusion of Ctrl or 125KD aging iEVs.…”
Section: Resultsmentioning
confidence: 99%
“…In cultured cytotrophoblasts, Let-7c is associated with reduced proliferation potential and syncytialization 56,57 . Let-7c is associated with the WNT/β-catenin signaling pathway in other progenitor cell types 58 . In cultured extravillous trophoblasts, miR-1290 promotes rearrangement of maternal endometrium via placental exosomes 59 .…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that miR-99a may regulate tumor cell proliferation through mTOR, AKT1 and FGFR3 [20][21][22], but detailed studies on the mechanisms of action remain lacking. In this study, MTT assay showed that up-regulating miR-99a inhibited the proliferation of glioma cells, but knocking it down promoted their proliferation.…”
Section: Discussionmentioning
confidence: 99%